2022
DOI: 10.1002/aenm.202200754
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Conducting Polypyrrole into a Polyimide COF for Carbon‐Free Ultra‐High Energy Supercapacitor

Abstract: Redox‐active covalent organic frameworks (COFs) store charges but possess inadequate electronic conductivity. Their capacitive action works by storing H+ ions in an acidic electrolyte and is typically confined to a small voltage window (0–1 V). Increasing this window means higher energy and power density, but this risks COF stability. Advantageously, COF's large pores allow the storage of polarizable bulky ions under a wider voltage thus reaching higher energy density. Here, a COF–electrode–electrolyte system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 73 publications
0
63
0
2
Order By: Relevance
“…1a). [39][40][41] It was followed by the other characteristic peaks from aromatic groups like triazine around 172 ppm (i) and aromatic peak around 151 ppm (h). The aliphatic peaks for the building blocks around 65 ppm (b) were intact.…”
Section: Resultsmentioning
confidence: 99%
“…1a). [39][40][41] It was followed by the other characteristic peaks from aromatic groups like triazine around 172 ppm (i) and aromatic peak around 151 ppm (h). The aliphatic peaks for the building blocks around 65 ppm (b) were intact.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a class of organic polymeric porous materials with crystalline and periodic structures, that is, covalent organic frameworks (COFs), have shown highly promising potential in the applications of heterogeneous catalysis, chemical sensing, bio-imaging, , and photodynamic therapy, proton conduction, and energy storage, as well as adsorption and separation to kinds of ions and molecules, including iodine. Due to their inherent porosity and strong covalent bonding of the organic components with light elements such as C, H, O, and N, COF materials not only show low density and relatively high stability but also display chemical tenability. For instance, functional organic moieties with photoresponsive activity, proton-transport properties, and even chiral centers have been introduced into the COFs during the syntheses of precursors or post-modification of the constructed frameworks for photocatalysis, proton conduction, , and asymmetric catalysis, respectively. Previous works on iodine adsorption revealed that by decorating the framework with nitrogen-rich groups, the adsorption capacity of iodine can be significantly improved. Thus, introducing nitrogen-rich groups into the COFs should be a feasible way for the fabrication of effective iodine adsorbents.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Vaidhyanathan and co‐workers further loaded redox‐active and conductive polypyrrole into COFs nanochannels and constructed a Ppy@COF hybrid, which exhibited a nearly 10 000‐fold increased electrical conductivity. [ 71 ] The synergies between polypyrrole and redox‐active imide linking bonds in the COF provided a high areal specific capacitance of 358 mF cm − 2 at 1 mA cm − 2 in a carbon‐free quasi‐solid‐state capacitor.…”
Section: Cofs For Supercapacitor Applicationsmentioning
confidence: 99%